(untitled) (Ameghiniana, 2013)
TRILOBITES FROM THIE CAMBRIAN OLISTOLITES OF THE LOS SOMBREROS FORMATION (ORDOVICIAN), PRECORDILLERA OF SAN JUAN, ARGENTINA. Trilobites from the exotic calcareous blocks contained in the Ordovician turbiditic sequence named Los Sombreros Formation are described and illustrated. The identified taxa are: Pentagnostus praecurrens (Westergard). Olenellus? sp., Olenoides sp., Kootenia sp., Chilometopus? tunelensis n. sp., Zacanthoides sp., Prozacanthoides n. sp., Prozacanthoides? sp, y Sombrerella argentina n. sp. The association present in a block at the base of the olistotromic complex, belongs lo the Olenellus Zone and indicates a late Early Cambrian age. The trilobites found in the western olistolitic block suggest an early Middle Cambrian age (Batuyariscus-Elrathina Zone in the North American biostratigraphical scale).